DESIGN OF PLANT FOR INDUSTRIAL PRODUCTION OF STYRENE IN KAZAKHSTAN - Ingkar, Gulnaz; Askarov, Almas; Bekken, Arailym; Issabek, Kuralay; Kalmakhanbet, Alikhan; Mels, Aizada (Nazarbayev University School of Engineering and Digital Sciences, 2025)
Styrene is a vital industrial chemical widely used in the production of polystyrene plastics and resins, which are essential across packaging, construction, automotive, and electronics industries. Its global demand continues to rise due to its versatility, lightweight nature, and cost-effectiveness. This capstone project focuses on the design of a chemical plant for the industrial-scale production of styrene, aiming to meet approximately 25% of the forecasted demand in the Commonwealth of Independent States (CIS) by 2027. The main application of the final 99.7% pure styrene product is styrene-butadiene-rubber (SBR). The project involves the complete development of the plant, from raw material input to final product output, emphasizing the design and integration of both major equipment and minor supporting units essential for continuous operation. Aspen Plus was utilized for process simulation and optimization, while economic feasibility, energy efficiency, and safety considerations were incorporated throughout the design. The result is a technically and economically viable plant layout that supports regional industrial growth and aligns with environmental and process safety standards.
Keywords: Styrene; Ethylbenzene dehydrogenation; Chemical process design; Aspen Plus; Plant economic analysis; Plant design; type of access: open access